The V4 and Ukraine Fight with Tax Frauds and Money Laundering [całość] - Balytyska, Mariia. Redakcja; Bohušová, Hana. Redakcja; Luty, Piotr. Redakcja (Publishing House of Wroclaw University of Economics and Business, 2025)
[The monograph presents a comprehensive exploration of the mechanisms, challenges, and strategies employed by the Visegrad Group countries and Ukraine to combat tax fraud and money laundering. The book is divided into nine chapters, each dedicated to a specific aspect of the overarching issue, such as blockchain technology as a tool to combat money laundering within the V4 countries and Ukraine, tax aggressiveness in corporate taxation, Financial Action Task Force compliance, tax security, VAT carousel frauds and taxation of Ukrainian refugees. Together, they offer insights into the legal, technological, and economic frameworks that shape the fight against financial crime in this region, emphasizing the importance of regional collaboration and innovation.] z zapowiedzi
Quote as: Balytska, M., Bohušová, H., & Luty, P. (Eds.). (2025). The V4 and Ukraine Fight with Tax Frauds and Money Laundering. Publishing House of Wroclaw University of Economics and Business.
s. 118
Keywords: tax fraud; tax aggressiveness; money laundering; blockchain; FATF